2003
DOI: 10.1017/s1367943003003123
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure in otter (Lutra lutra) populations in Europe: implications for conservation

Abstract: During the twentieth century otter (Lutra lutra) populations in central and western Europe declined and became fragmented because of habitat alterations, chemical pollution and direct persecution. In this study we used microsatellites to describe spatial patterns of genetic diversity and subdivision in otters from eight populations in Europe. Genetic diversity was moderately high within populations (He = 0.45-0.77), and significantly partitioned among locations (F ST = 0.17; R ST = 0.16; P < 0.001). A Bayesian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
53
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 35 publications
(33 reference statements)
9
53
3
Order By: Relevance
“…In this context, the total number of 14 control region haplotypes now described for the otter is low, but not extremely so. Also the haplotypic diversity we found is consistent with a previous microsatellite analysis of Ireland (H E Ireland = 0.77; Rest of Europe = 0.45-0.74; Randi et al 2003). Therefore, the relatively high diversity in Ireland may be indicative of the historical diversity of the species, and it is likely that further sampling in regions where populations have been relatively stable will reveal additional haplotypes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this context, the total number of 14 control region haplotypes now described for the otter is low, but not extremely so. Also the haplotypic diversity we found is consistent with a previous microsatellite analysis of Ireland (H E Ireland = 0.77; Rest of Europe = 0.45-0.74; Randi et al 2003). Therefore, the relatively high diversity in Ireland may be indicative of the historical diversity of the species, and it is likely that further sampling in regions where populations have been relatively stable will reveal additional haplotypes.…”
Section: Discussionsupporting
confidence: 90%
“…Randi et al (2003) found high microsatellite genetic variation in the Irish population, possibly as a result of its more stable demographic history. It is possible that this is also reflected in the mitochondrial genome.…”
Section: Introductionmentioning
confidence: 91%
“…This haplotype has now been identified as the most common in both Germany (Lut3 n = 42, 55.3% Cassens et al 2000) and England, although our sample distribution is biased towards the east of England. It is still evident however that Europe as a whole has relatively low mitochondrial diversity (h = 0.4712 for all known European sequences), although there is evidence of other countries showing higher levels of nuclear genetic diversity, for example Ireland (Randi et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The intra-specific taxonomy of otter populations is uncertain, because the species exhibits unusually low levels of mtDNA variation, and shows almost no mtDNA geographic structure (Effenberger and Suchentrunk 1999;Mucci et al 1999;Cassens et al 2000;Arrendal et al 2004;Ferrando et al 2004;Ketmaier and Bernardini 2005;Pérez-Haro et al 2005;Finnegan and Néill 2009;Stanton et al 2009). Autosomal microsatellites are polymorphic in otters, but the populations studied so far showed little geographical differentiation also at the nuclear level (Dallas et al 1999;Pertoldi et al 2001;Dallas et al 2002;Randi et al 2003;Arrendal et al 2004;Hajkova et al 2007;Janssens et al 2008). The scope of published studies was limited by restricted geographical sampling collections.…”
Section: Introductionmentioning
confidence: 99%